Uniting, Leading, and Ruling: Social Skill and the Construction of Local Social Orders - Chernysh, Anna (Journal of Economic Sociology, 2014)
The review considers a new theory of strategic action fields provided in the book “ATheory of Fields”. The author analyzes its basic elements— new as well as borrowed from other theories, and its significance for the development of organizational theory, the theory of social movements, institutional theory and economic sociology. The last part of the text criticizes some debatable theses of this theory. Theory of strategic action fields discusses the issue of the local social orders formation. The authors represent all social orders as fields, which consist of the following actors: incumbents; challengers and internal governance units. All fields are embedded in a broader field environment. It gives the most significant incentives to changes of the organizational models dominant in the fields in question. Incentives to changes are converted into changes in the case of mobilization for the collective action. It is crucial to have special social skill for the start of mobilization process. Authors define social skill as an ability to understand other actors and manage them by creating shared meanings and identities for themselves and others. Thus the authors shift their attention from the control based on the resources or power to the ability to voluntary cooperation. Social skill and the ability to voluntary cooperation are the consequence of “existential functions of the social”, the important innovation of this theory.